2020
DOI: 10.1166/jbn.2020.2887
|View full text |Cite
|
Sign up to set email alerts
|

Combined Detection of Exosome Concentration and Tumor Markers in Gastric Cancer

Abstract: It has been an established fact that exosomes act as a mediator in tumor microenvironment as well as participate actively in intercellular communication between cancer cells. Exosomes carry a variety of molecular cargoes that prevent cyclic degradation and represent the cells of their origin. In this study, the difference in expression levels of exosomes was measured for diagnosis of gastric cancer. We isolated exosomes from plasma by size-selective method. The morphology of the exosomes was characterized by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Previous studies have reported considerable progress in the field of liquid biopsy, particularly some nanomaterial-based liquid biopsy techniques ( Zhang P et al, 2019 ; Tian et al, 2019 ; Huang et al, 2020 ; Xia et al, 2020 ; Chen et al, 2021 ; He et al, 2021 ). On this basis, some studies have significantly improved the sensitivity of liquid biopsies, while others have looked at reducing the amount of fluid used in this process ( Huang et al, 2019 ; Li et al, 2019 ; Kim et al, 2020 ; Jiang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported considerable progress in the field of liquid biopsy, particularly some nanomaterial-based liquid biopsy techniques ( Zhang P et al, 2019 ; Tian et al, 2019 ; Huang et al, 2020 ; Xia et al, 2020 ; Chen et al, 2021 ; He et al, 2021 ). On this basis, some studies have significantly improved the sensitivity of liquid biopsies, while others have looked at reducing the amount of fluid used in this process ( Huang et al, 2019 ; Li et al, 2019 ; Kim et al, 2020 ; Jiang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Most of the early studies on EVs isolation were carried out by obtaining materials from cell culture medium, and humoral derived EVs (such as urine, blood, malignant ascites) have great scientific and clinical significance. A large number of studies have proved that exosome surface proteins, endogenous proteins and nucleic acids isolated from body fluids of various cancer patients are expected to be biomarkers for prediction, diagnosis, staging, radiotherapy and chemotherapy treatment response and prognosis [92], such as glioma [93]; Esophageal cancer [94]; Gastric cancer [95]; Pancreatic cancer [96,97]; Hepatocellular carcinoma [98]; Colorectal cancer [99]; Lung cancer [100]; Lung adenocarcinoma [101]. Non-small cell lung cancer [102]; Bladder cancer [103]; Prostate cancer [104]; Ovarian cancer [105,106]; Breast cancer [107], etc.…”
Section: Application Of Exosomes As Biomarkers In Breast Cancermentioning
confidence: 99%
“…Therefore, serum level can reflect the functional status of the gastric mucosa and is gradually used in the clinical diagnosis of early gastric cancer (19). The study shows that the occurrence and development mechanism of cancer is complex and biological characteristics, including tumor markers reflecting the presence of the tumor can indicate the nature of the tumor (20). CA199 is a class of glycoproteins with significantly elevated levels in malignant tumors like the gastrointestinal, hepatobiliary, and pancreas (21).…”
Section: Serum Pgi Pgii Ca199 Levels Were Compared Between the Two Gr...mentioning
confidence: 99%